Influence of sex on the profile of acute coronary syndrome: a tertiary care hospital based study from the Sub-Himalayan region in North India - Kapoor, Dhiraj; Gupta, Pankaj; Sontakke, Tushar; Agarwal, Vishnu; Sunder, Shyam; Sharma, Rupinder; Jearth, Vineet (International Journal of Research in Medical Sciences, 2017)
Background: Coronary events presents about ten years later in women than men. There exist distinct gender differences in terms of presentation of symptoms, validity of diagnostic tests and complications. Methods: The study was conducted in the department of medicine R.P. Govt. Medical College (RPGMC) Himachal Pradesh. Consecutive 300 patients of acute coronary syndrome from June 2011 to June 2012 were included in the study. Demographical profile was recorded with focused clinical examination and relevant investigation with lipid profile was done. Results:Among the study population of 300 individuals, 201 (67%) were males and 99 (33%) were females. The mean age among male patients was 61.3±11.7 years and in female patients the mean age was 65.6±11.20 years. 68.8% of females presented after 60 yrs of age. Dyslipidemia was the commonest risk factor followed by hypertension and obesity. 12.2% of female patients were smokers. Chest pain was the commonest presenting symptom seen in 82% cases. There was mean delay of 31.0±54.5 hrs in the presentation of females for treatment. ST Elevated Myocardial Infarction occurred less frequently in females. Conclusions: Acute coronary syndrome is more age dependent in females. The predominance of dyslipidemia, hypertension and obesity as risk factors gives a message for primary care physicians to create awareness for the prevention of Acute Coronary Syndrome. The atypical symptoms should be recognised early which should further prevent the delay in presentation.